Teaching with the Test : Experimental Evidence on Diagnostic Feedback and Capacity Building for Public Schools in Argentina - de Hoyos, Rafael; Ganimian, Alejandro J.; Holland, Peter (World Bank, Washington, DC, 2017)
Despite the recent growth in the number of large-scale student assessments, there is little evidence on their potential to inform improvements in school management and classroom instruction in developing countries. This study conducted an experiment in the Province of La Rioja Argentina, that randomly assigned 105 public primary schools to: (a) a "diagnostic feedback" group in which standardized tests were administered in math and reading comprehension at baseline and two follow-ups and the results were made available to the schools through user-friendly reports; (b) a “capacity-building” group for which schools were provided with the reports and also workshops and school visits for supervisors, principals, and teachers; or (c) a control group, in which the tests were administered only at the second follow-up. After two years, diagnostic feedback schools outperformed control schools by .34 and .36 standard deviations (SD) in third grade math and reading, and by .28 and .38 SD in fifth grade math and reading. The principals at these schools were more likely to report using assessment results for management decisions, and students were more likely to report that their teachers engaged in more instructional activities and improved their interactions with them. Capacity-building schools saw more limited impacts due to lower achievement at baseline, low take up, and little value-added of workshops and visits. However, in most cases the results cannot discard the possibility that both interventions had the same impact.